Iodine deficiency and schooling attainment in Tanzania - Field, Erica Marie; Robles, Omar; Torero, Máximo (American Economic Association, 2009)
Cognitive damage from iodine deficiency disorders (IDD) has important implications for economic growth through its effect on human capital. To gauge the magnitude of this influence, we evaluate the impact on schooling of reductions in IDD from intensive iodine supplementation in Tanzania. Our findings suggest a large effect of in utero iodine on cognition and human capital: treated children attain an estimated 0.35–0.56 years of additional schooling relative to siblings and older and younger peers. Furthermore, the effect appears to be substantially larger for girls, consistent with laboratory evidence indicating greater cognitive sensitivity of female fetuses to maternal thyroid deprivation. (JEL I12, I21, J16, O15)